Preoperative prediction of prosthesis size using cross sectional echocardiography in patients requiring aortic valve replacement. Issue 5 (May 1985) - Mackay, A; Been, M; Rodrigues, E; Murchison, J; de Bono, D P
Abstract : In 43 patients who underwent aortic valve replacement for aortic stenosis with or without regurgitation the accuracy of preoperative left ventricular angiography, parasternal long axis cross sectional echocardiography of left ventricular outflow tract and proximal ascending aorta, and M mode echocardiography of aortic root in predicting aortic root size and thereby prosthesis size was compared. Cross sectional echocardiographic measurements and angiographic measurements of aortic root correlated well with prosthesis size, with over two thirds of the indirect measurements being within 2 mm of prosthesis diameter. M mode echocardiography did not yield useful predictive information. Non-invasive preoperative evaluation of patients likely to require aortic valve replacement may be usefully extended to include aortic root dimensions measured by cross sectional echocardiography.